Prospects of oral anticoagulant therapy in patients with atrial fibrillation and chronic anemia: a narrative review - Tatyana S. Degtyareva; Kristina G. Pereverzeva; Sergey S. Yakushin; Natalia N. Peregudova (КардиоСоматика)
Anticoagulant therapy for atrial fibrillation (AF) plays an important role in preventing thromboembolic events. This review discusses anticoagulant therapy in patients with AF and chronic anemia of varying severity. The search was carried out in PubMed and Library electronic databases from 2010 to 2023. Based on the analysis of full text literature, the authors concluded that currently oral anticoagulants in patients with AF and mild chronic anemia (Hb 90 g/L) and, according to some studies, in patients with moderate anemia (Hb 80 g/L) are considered reasonable. Patients with AF and moderate anemia (Hb 71–80 g/L) require an individualized approach to therapy with oral anticoagulants, since its benefit is not obvious in this subgroup, and the risk of hemorrhagic complications is high. Currently, severe anemia is a contraindication to oral anticoagulants in patients with AF.